Absolute cardiovascular risk and GP decision making in TIA and minor stroke. (10th September 2014) - Clarey, Jamie; Lasserson, Daniel; Levi, Christopher; Parsons, Mark; Dewey, Helen; Barber, P Alan; Quain, Debbie; McElduff, Patrick; Sales, Milton; Magin, Parker
Abstract : Background: Transient ischaemic attacks (TIA) and minor strokes (TIAMS) have the same pathophysiological mechanism as stroke and carry a high risk of recurrent ischaemic events. Diagnosis of TIAMS can be challenging and often occurs in general practice. Absolute cardiovascular risk (ACVR) is recommended as the basis for vascular risk management. Consideration of cardiovascular risk in TIAMS diagnosis has been recommended but its utility is not established. Objectives: Firstly, to document the ACVR of patients with incident TIAMS and with TIAMS-mimics. Secondly, to evaluate the utility of ACVR calculation in informing the initial diagnosis of TIAMS. Methods: The International comparison of Systems of care and patient outcomes in minor Stroke and TIA (InSiST) study is an inception cohort study of patients of 17 Australian general practices presenting as possible TIAMS. An expert panel determines whether participants have had TIAMS or TIAMS-mimics. ACVR was calculated at baseline for each participating patient. In this cross-sectional baseline analysis, ACVR of TIAMS and TIAMS-mimics were compared univariately and, also, when adjusted for age and sex. The diagnostic utility of ACVR was evaluated via receiver operating characteristic (ROC) curves. Results: Of 179 participants, 87 were adjudicated as TIAMS. The presence of motor and speech symptoms and body mass index were associated with a diagnosis of TIAMS. ACVR was associated with TIAMS diagnosis on univariate analysis, but not when age- and sex-adjusted. ACVR did not significantly improve area under ROC curves beyond that of age and sex. Conclusion: In patients presenting with transient or minor neurological symptoms, calculation of ACVR did not improve diagnostic accuracy for TIAMS beyond that of age and sex.